Home care in Europe: a systematic literature review - Fagerström Cecilia; Francke Anneke L; Bouman Ans; Kringos Dionne S; Boerma Wienke GW; Genet Nadine; Melchiorre Maria; Greco Cosetta; Devillé Walter (BMC, 2011)
Abstract Background Health and social services provided at home are becoming increasingly important. Hence, there is a need for information on home care in Europe. The objective of this literature review was to respond to this need by systematically describing what has been reported on home care in Europe in the scientific literature over the past decade. Methods A systematic literature search was performed for papers on home care published in English, using the following data bases: Cinahl, the Cochrane Library, Embase, Medline, PsycINFO, Sociological Abstracts, Social Services Abstracts, and Social Care Online. Studies were only included if they complied with the definition of home care, were published between January 1998 and October 2009, and dealt with at least one of the 31 specified countries. Clinical interventions, instrument developments, local projects and reviews were excluded. The data extracted included: the characteristics of the study and aspects of home care 'policy & regulation', 'financing', 'organisation & service delivery', and 'clients & informal carers'. Results Seventy-four out of 5,133 potentially relevant studies met the inclusion criteria, providing information on 18 countries. Many focused on the characteristics of home care recipients and on the organisation of home care. Geographical inequalities, market forces, quality and integration of services were also among the issues frequently discussed. Conclusions Home care systems appeared to differ both between and within countries. The papers included, however, provided only a limited picture of home care. Many studies only focused on one aspect of the home care system and international comparative studies were rare. Furthermore, little information emerged on home care financing and on home care in general in Eastern Europe. This review clearly shows the need for more scientific publications on home care, especially studies comparing countries. A comprehensive and more complete insight into the state of home care in Europe requires the gathering of information using a uniform framework and methodology.